Conflicting priorities in the promotion of gender equality in Ethiopia: Uneven implementation of land registration and the impact on women's land rights - Tom Lavers (United Nations Research Institute for Social Development (UNRISD), 2014)
The current Ethiopian government originated in a Marxist revolutionary movement, which early in its struggle against the Derg regime recognized the widespread discrimination against women in Ethiopian society and placed gender emancipation at the centre of its revolutionary strategy. While political expediency and confrontation with patriarchal Ethiopian society has at times challenged its commitment to women, the EPRDF has, nevertheless, introduced a number of reforms which aim to promote gender equality. This includes recognition of equality between men and women in land rights, and a land registration programme that requires the names of both husbands and wives on certificates. This paper examines the gendered impacts of these reforms through analysis of three village-level case studies based on fieldwork conducted in 2009-10. The cases highlight the contingent nature of gender outcomes based on local state-society relations, and the governments political and economic priorities, resulting in considerable variation within Ethiopia.
Keywords: 330